Screening of probiotics bacteria from coral reef using co-culture method for controlling vibriosis in tiger shrimp (Penaeus monodon) larvae - Ade Dwi Sasanti; Widanarni .; Sukenda . (Jurnal Akuakultur Indonesia)
ABSTRACT